Assessment of Alkali-Induced Heaving in Soil and its Stabilisation using Additives through Electrokinetics - Mandal, Manish Kumar (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Assessment of Alkali-; Induced Heaving in Soil; Stabilisation using Additives; through Electrokinetics